Long-term immune changes after COVID-19 and the effect of BCG vaccination and latent infections on disease severity - Bendíčková, Kamila; Papatheodorou, Ioanna; Blažková, Gabriela; Helán, Martin; Haláková, Michaela; Bednář, Petr; Spearing, Erin; Obermannová, Lucie; Štíchová, Julie; Heroldová, Monika Dvořáková; Tomáš, Tomáš; Panovský, Roman; et al. (Clinical & translational immunology, 2025)
OBJECTIVES: Several years after the COVID-19 pandemic, the impact of SARS-CoV-2 on immunity and the potential protective role of Bacillus Calmette-Guérin (BCG) vaccination through trained immunity remain a subject of investigation. This study aimed to determine the long-term impact of SARS-CoV-2 on immune cells and the association between BCG vaccination, latent infections and COVID-19 severity and sepsis progression. METHODS: We conducted a prospective analysis of patients who recovered from mild/severe/critical COVID-19 (n = 97, 3-17 months after COVID-19) and sepsis patients (n = 64). First, we assessed the impact of COVID-19 and its severity on immune cell frequencies and expression of functional markers. Further, we analysed plasma titres of anti-Toxoplasma gondii/cytomegalovirus/BCG antibodies and their association with COVID-19 severity and sepsis outcome. To examine monocyte responses to secondary challenge, monocytes isolated from COVID-19 convalescent patients, BCG vaccinated and unvaccinated volunteers were stimulated with SARS-CoV-2 and LPS. RESULTS: Post-COVID-19 patients showed immune dysregulation regardless of disease severity characterised by altered expression of activation and functional markers in myeloid (CD39, CD64, CD85d, CD11b) and lymphoid cells (CD39, CD57, TIGIT). Strikingly, post-critical COVID-19 patients showed elevated expression of CD57 in CD8+ T cells compared to other severity groups. A trend toward improved outcomes in BCG-seropositive COVID-19/sepsis patients was observed, although this may be confounded by age differences between groups. In contrast, the monocyte response to stimulation appeared unaffected by COVID-19 severity. CONCLUSION: These findings highlight the long-term alterations of immune cells in post-COVID-19 patients, emphasising the substantial impact of COVID-19 on immune function.
Keywords: immune cells; Toxoplasma; cytomegalovirus; Bacillus Calmette–Guérin (BCG) vaccination; sepsis; COVID‐19